Towards substitution of invasive telemetry: an integrated home cage concept for unobtrusive monitoring of objective physiological parameters in rodents - Mösch, Lucas; Kunczik, Janosch; Breuer, Lukas; Merhof, Dorit; Gass, Peter; Potschka, Heidrun; Zechner, Dietmar; Vollmar, Brigitte; Tolba, René; Häger, Christine; Bleich, André; Czaplik, Michael; et al. (PLOS ONE, 2023)
This study presents a novel concept for a smart home cage design, tools, and software used to monitor the physiological parameters of mice and rats in animal-based experiments. The proposed system focuses on monitoring key clinical parameters, including heart rate, respiratory rate, and body temperature, and can also assess activity and circadian rhythm. As the basis of the smart home cage system, an in-depth analysis of the requirements was performed, including camera positioning, imaging system types, resolution, frame rates, external illumination, video acquisition, data storage, and synchronization. Two different camera perspectives were considered, and specific camera models, including two near-infrared and two thermal cameras, were selected to meet the requirements. The developed specifications, hardware models, and software are freely available via GitHub. During the first testing phase, the system demonstrated the potential of extracting vital parameters such as respiratory and heart rate. This technology has the potential to reduce the need for implantable sensors while providing reliable and accurate physiological data, leading to refinement and improvement in laboratory animal care.
Gesehen am 21.08.2024